Biologically inspired bearing-only navigation and tracking - Kumar, Vijay R.; Loizou, Savvas (My University, 2007)
In this paper we develop controllers that are used for the control of individual or groups of vehicles based only on sensors that provide bearing information. Our inspiration is derived from the observation that many ant species use landmark retinal positions to navigate without having any range information. This is specially relevant to vision-based controllers for vehicles because cameras provide very good bearing information but relatively poor range information. We present a provably correct bearing-only navigation controller and a methodology for tracking that lends itself to control of formations. The proposed feedback controllers are shown to have analytically guaranteed properties. The effectiveness of the proposed controllers is demonstrated through computer simulations.
Keywords: Computer simulation; Navigation; Biosensors; Automatic control